Teaching Afrofuturisms as American Cultural Studies - Lavan, Makeba (Radical Teacher, 2022)
Kodwo Eshun asserts that “Afrofuturism studies the appeals that black artists, musicians, critics, and writers have made to the future, in moments where any future was made difficult for them to imagine.” Afrofuturism allows African diasporic writers to imagine new and alternate cultural elements in hopes that these will take root in the collective consciousness and shift the cultural paradigm towards true citizenship and equity. It is this main idea that we explored over two semesters (spring 2020 and Spring 2021) of classes taught online in the wake of brutal state sanctioned murders, subsequent uprisings and a global pandemic. As we learned to maneuver these changes, students facilitated lateral learning across discussion groups and questions, asynchronous group meetings, and collaborations with other classes in a class modeled after the Black Radical Tradition.